Comparative analysis of opioid use in sickle cell crisis in an urban facility in Ghana - Marian Opoku‐Agyakwa; Henry J. Lawson; Edeghonghon Olayemi (eJHaem, 2023)
Abstract Vaso‐occlusive crises (VOC) is common and opioids are the treatment of choice.This study compared parenteral pethidine and morphine in the elimination/reduction of pain in acute VOC to tolerable levels. This open‐label randomized study compared intravenous morphine 5 mg 4 hourly to intramuscular pethidine 75 mg 4 hourly. Eighty‐two consenting adult sickle cell disease participants were recruited from the Korle‐Bu Polyclinic. (Forty‐one participants in each arm). There were 42 male and 40 female participants. Median age was 25 years. Pethidine participants totalling 31.7% (13/41) and 53.7% (22/41) in the morphine arm had a sustained response within 6 h, p = 0.027. In the pethidine and morphine arms 60.0% (24/40) and 62.5% (25/40) of participants respectively achieved adequate pain control within 72 h of initiating therapy, p = 0.296. Most participants, 96.3% (79/82) had no side effects to opioids. The commonest side effects were generalized pruritus, nausea and vomiting, and headaches. More pethidine than morphine participants experienced side effects 29.3% and 22.0% respectively; p = 0.448. In conclusion, more morphine participants achieved a sustained pain response compared to the pethidine participants. There was no difference in the tolerability and side effect profile of the opioids. No participant experienced respiratory suppression.